Banking on Politics - Raddatz, Claudio (2012)
This paper presents new data from 150 countries showing that former cabinet members, central bank governors, and financial regulators are many orders of magnitude more likely than other citizens to become board members of banks. Countries where the politician-banker phenomenon is more prevalent have higher corruption and more powerful yet less accountable governments, but not better functioning financial systems. Regulation becomes more pro-banker where this happens more often. Furthermore, a higher fraction of the rents that are created accrue to bankers, former politicians are not more likely to be directors when their side is in power, and banks are more profitable without being more leveraged. Rather than supporting a public interest view, the evidence is consistent with a capture-type private interest story where, in exchange for a non-executive position at a bank in the future, politicians provide for beneficial regulation.